Pengaruh Model Pembelajaran Kooperatif Learning Tipe Studens Teams Achievement Division (STAD) Terhadap Hasil Belajar Ekonomi Siswa Kelas XI IPS-1 SMA Swasta Masehi GBKP Berastagi - Br Tarigan, Mika Deriani; Meitriana, Made Ary (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study was conducted so that researchers can determine the effect of the cooperative learning model of students' teams achievement division (STAD) on the economics learning outcomes of class XI IPS-1 students at SMA Swasta Masehi GBKP Berastagi FY 2021/2022. This study uses a quasi-experimental type of research (quasi-experimental). The subjects of this study were students of class XI IPS-1 while the objects of this study were learning outcomes and cooperative learning models of students' teams achievement division (STAD) type. This research design uses the one group pretest-posttest or pre-experimental. The results of the study indicate that there is an effect of the use of the cooperative learning model type student achievement division (STAD) on the economic learning outcomes of class XI IPS-1 students at SMA Swasta Masehi GBKP Berastagi FY 2021/2022. The results of the t-test analysis show the t-value of 21.211 with a significance value of 0.00 <0.05, so Ha is accepted or the alternative decision is accepted and H0 is rejected or the null hypothesis is rejected.